Slashchuk V.O. Definition of the coefficient of effect for cooperative modes for friction process in the contact dynamic system. - Слащук, В. О. (Problems of Tribology, 2018)
In this paper, the change in the coefficient of influence of nonlocal modes in the process of low-amplitude friction is investigated. It is established that when friction surfaces are generated waves of the mechanical system, which can affect the transition of energy from one mode friction to another, which significantly changes the nature and intensity of wear of surfaces. The method of determining the coefficient of influence of nonlocal modes is given, taking into account the hybrid nature of these mods. Actual of the problem of ensuring the reliability of nominally-immovable connections is to fix the processes occurring in the contact area of the surfaces. In particular, the determination of the actual state of the connection of the connection without stopping the work or unloading the workstation. The described method of analysis of hysteresis loops does not require stopping of the mechanical system for the removal of indicators, the analysis of loops is easy to calculate. The real dynamic contact interaction differs from the kinematic interaction by the presence of the given modes of motion, which form a certain dynamic cooperative form of motion, affecting the nature of the teeth, which is manifested through the coefficient. The real dynamic contact interaction differs from the kinematic interaction by the presence of the given modes of motion, which form a certain dynamic cooperation. At the final stage of wear, the manifestation of third-party mods is intensified. He quantitatively manifests itself in the growth of the factor of 2-3 times. This indicates a qualitative change in the nature of the dynamic interaction, when the non-standard modes in magnitude are compared with the main (given). The modification of surfaces is capable of increasing the resource (duration) of a non-mortar immobile friction connection by an order of magnitude. But the selection of modification parameters must be based on experimental studies.